Digital Communication Planning through Instagram for Product Marketing at Cavalry Gading Serpong Showroom - Alvina Deshamti; Agung Putra Mulyana (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze digital communication planning through Instagram to market MAKA Cavalry products at the MAKA Showroom in Gading Serpong . As a local automotive company producing electric motorcycles, MAKA Motors faces significant challenges from competitors and the importance of building brand awareness through digital media. The study used a qualitative approach using Regina Luttrell's Circular Model of SOME (Share, Optimize, Manage, Engage) as the foundation for its digital communication strategy. Data were collected through participant observation, in-depth interviews, and documentation of the activity of the @ makamotorsgadingserpong_vina Instagram account. The results show that a structured digital communication plan through Instagram can increase visibility, audience interaction, and brand image of MAKA Cavalry products. The strategies implemented include creating relevant and visually appealing content, optimizing posting times and hashtags, consistent account management, and encouraging audience engagement through two-way interactions. This study highlights the importance of evaluating Instagram insights and adapting content to suit the needs of the target audience. These findings can serve as a reference for the local automotive industry in optimizing social media as a marketing tool for environmentally friendly technology-based products.